2009
DOI: 10.1152/ajpgi.00127.2009
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II modulates hepatic fibrosis and portal hemodynamic alterations in rats

Abstract: The influence of circulating urotensin II (UII) on liver disease and portal hypertension is unknown. We aimed to evaluate whether UII executes a pathogenetic role in the development of hepatic fibrosis and portal hypertension. UII was administered by continuous infusion over 4 wk in 20 healthy rats divided into three treatment groups, controls (saline, n = 7), low dose (UII, 1 nmol·kg−1·h−1, n = 8), and high dose (UII, 3 nmol·kg−1·h−1, n = 5). Hemodynamic parameters and morphometric quantification of fibrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Furthermore, urotensin II concentrations correlate with the severity of disease and with portal pressure gradient suggesting that it is likely to be of relevance to the pathology of ACLF [46]. Studies in animal models have shown that infusion of urotensin II into normal rats can promote fibrogenesis, while also increasing portal pressure [47], whereas inhibition of the urotensin II receptor in cirrhotic rats lowered portal pressure, while also increasing splanchnic vascular resistance [48]. Thus, inhibition of urotensin II shows promise as a novel target for therapy of portal haemodynamic derangements in advanced cirrhosis, but clinical studies are awaited.…”
Section: Activation Of the Sympathetic And Neuro-humoral Systemsmentioning
confidence: 99%
“…Furthermore, urotensin II concentrations correlate with the severity of disease and with portal pressure gradient suggesting that it is likely to be of relevance to the pathology of ACLF [46]. Studies in animal models have shown that infusion of urotensin II into normal rats can promote fibrogenesis, while also increasing portal pressure [47], whereas inhibition of the urotensin II receptor in cirrhotic rats lowered portal pressure, while also increasing splanchnic vascular resistance [48]. Thus, inhibition of urotensin II shows promise as a novel target for therapy of portal haemodynamic derangements in advanced cirrhosis, but clinical studies are awaited.…”
Section: Activation Of the Sympathetic And Neuro-humoral Systemsmentioning
confidence: 99%
“…This phenomenon seems not to be a feature of cirrhosis, but of portal hypertension. Portal hypertension seems to induce vascular and hepatic upregulation of UT and fibrosis, as shown recently by Kemp et al (25). Furthermore, a limitation of our study is that the patients with cirrhosis and portal hypertension are only a fraction of all patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 66%
“…patients, suggesting that U-II may play a significant role in the cardiac dysfunction and remodeling associated with this condition (4,12). Our group has demonstrated that U-II infusion in healthy rats can increase portal pressure and induce an increase in hepatic fibrosis (9). However, the direct effects of U-II on the myocardium have not been evaluated extensively.…”
Section: Discussionmentioning
confidence: 99%
“…hypertrophic modulator, the intracellular mechanism of action of U-II in cardiac cells has not been explored extensively (9,13,15,24,27,29).…”
mentioning
confidence: 99%